(untitled) (Journal of Advanced Research in Journalism & Mass Communication, 2018)
Media Metrics is an innovative textbook by Professor Manoj Dayal published by Sage Publications India Pvt Ltd New Delhi. It is an irresistible source of knowledge in the field of media and communication research. The book explains media metrics and their application in quantitative mass communication research. It is a comprehensive introduction to the application of statistical tools and techniques in media research. It is a pioneering book on media metrics. It is easily readable and gives examples from media studies wherever required. The book largely explains the relationship between key media sources which include print, electronic, public relations, advertising, social media etc. The book explains scientific methods of data collection and their analysis by using statistics and mathematics. How to cite this article: Tewari SK. An Innovative Book on Media Research. J Adv Res Jour Mass Comm 2018; 5(3): 48.